Dialog sokratejski jako metoda poradnicza w pracy coacha = Socratic dialogue as a counseling method in the work of a coach - Majewska, Lucyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The modern world, shrouded in uncertainty, social unrest and moral crisis, has created new spaces for psychologists, coaches, personal trainers, and philosophical counselors to develop methods of psychological and moral assistance adapted to the present times. In this article, I argue that philosophy is functional and useful, not confined to scholarly deliberations.
Keywords: praca coacha; dialog; dialog sokratejski; prawda; filozofia praktyczna; etyka praktyczna; coaching; coaches; dialogue; Socratic dialogue; truth; practical philosophy; practical ethics; counseling